SIGNAL WARNING LIGHTS ON VEHICLES for driving on the freeway - Aqwam Rosadi Kardian (JAKSTIK Journal, 2006)
Use of signal lights that can be mounted on the rear of the car to drive on the freeway, especially at night. This lamp gives a signal to other cars approaching from behind. If the distance from the rear of the car too close then gave the signal light will blink to warn that cars could keep his distance. This lamp is also used to signal when the car was stopped on the side of the freeway.Â  This signal lights work process is to use a light sensor. If the received light from the headlights approaching from behind the lights will blink for 30 seconds until the car from behind is no longer too close or have preceded. This lamp uses two counter Time Integrated Circuit (IC-NE555), phototransistor, transistors, resistors, capacitors, Ligh Emitting Diode (LED) and battery as a power supply.